2015
DOI: 10.2196/mhealth.4603
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based and Mobile Delivery of an Episodic Future Thinking Intervention for Overweight and Obese Families: A Feasibility Study

Abstract: BackgroundThe bias toward immediate gratification is associated with maladaptive eating behaviors and has been cross-sectionally and prospectively related to obesity. Engaging in episodic future thinking, which involves mental self-projection to pre-experience future events, reduces this bias and energy intake in overweight/obese adults and children. To examine how episodic future thinking can be incorporated into clinical interventions, a Web-based system was created to provide training for adults and childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
142
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(147 citation statements)
references
References 45 publications
(49 reference statements)
3
142
0
2
Order By: Relevance
“…Although estimates of time required for task completion could not be obtained in the present study due to constraints of the software platform (Qualtrics), prior data indicate that this task can be completed rapidly (25 s; Koffarnus & Bickel 2014), making it uniquely well suited to examine delay discounting non-intrusively and iteratively in the natural environment. The ability to measure real-time, EFT-dependent changes in delay discounting in the real world may enhance our understanding of mechanisms underlying this interventionā€™s effects on dietary and weight control (Sze et al 2015; Oā€™Neill et al 2016) and other maladaptive behaviors such as alcohol use (Snider et al 2016) or cigarette smoking (Stein et al 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although estimates of time required for task completion could not be obtained in the present study due to constraints of the software platform (Qualtrics), prior data indicate that this task can be completed rapidly (25 s; Koffarnus & Bickel 2014), making it uniquely well suited to examine delay discounting non-intrusively and iteratively in the natural environment. The ability to measure real-time, EFT-dependent changes in delay discounting in the real world may enhance our understanding of mechanisms underlying this interventionā€™s effects on dietary and weight control (Sze et al 2015; Oā€™Neill et al 2016) and other maladaptive behaviors such as alcohol use (Snider et al 2016) or cigarette smoking (Stein et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Adapting these methods for use in natural settings has shown that EFT holds promise as a targeted weight loss treatment. For example, EFT has been used outside the laboratory to effectively reduce energy intake when administered both acutely (Oā€™Neill et al 2016) and as part of a web-based treatment to aid in dietary and weight control (Sze et al 2015). Indeed, such covariance between EFT, delay discounting, and eating behavior further supports an etiological role of delay discounting in obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Public health practitioners and researchers are increasingly harnessing mobile technology to enhance the reach and effectiveness of evidence-based interventions [1-3]. Equipping members of a target population to deliver effective public health messaging to peers is an established approach in substance abuse prevention, human immunodeficiency virus prevention, and health promotion [4-7], and is promising for suicide prevention [8].…”
Section: Introductionmentioning
confidence: 99%
“…Text4Strength uses text-based peer testimonials and other types of text messages to introduce high school students to Sources of Strength concepts and extends Sources of Strength by also introducing emotional skills associated with decreased depressive symptoms and lower suicide risk [14-17]. Text messaging is a logical medium for disseminating messages because it is the dominant mode of communication for youth [18] and has strong empirical support for delivering health interventions [2,3,19-25]. The current version of Text4Strength specifically targets ninth graders because research indicates an increase in emotional and behavioral problems between ages 14 and 15, when most students are starting high school [26].…”
Section: Introductionmentioning
confidence: 99%